2019
DOI: 10.2147/jpr.s195117
|View full text |Cite
|
Sign up to set email alerts
|

<p>Decreased expression of lncRNA Malat1 in rat spinal cord contributes to neuropathic pain by increasing neuron excitability after brachial plexus avulsion</p>

Abstract: Purpose: Neuropathic pain (NP) is a challenging clinical problem due to its complex pathogenesis. In our previous study using microarray, we found that the levels of lncRNA Malat1 were decreased in the spinal cord of NP rat after brachial plexus avulsion, but its contribution to NP remain unclear. The purpose of this study was to investigate its role in the pathogenesis of NP. Methods: In the NP model of complete brachial plexus avulsion rat, spinal cords were harvested, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…As the most serious form of peripheral nerve injury, brachial plexus root avulsion (BPRA) results in the paralysis of ipsilateral upper limbs, and it is usually caused by high-energy trauma, such as traffic accidents and gunshots ( Meng et al, 2019 ). BPRA-caused pain is largely featured by the quick onset of pain (an effect presenting right away following the injury) and the long-lasting progress of neuropathic pain, which is described as crushing, squeezing, or burning ( Chen et al, 2019 ; Wang T. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the most serious form of peripheral nerve injury, brachial plexus root avulsion (BPRA) results in the paralysis of ipsilateral upper limbs, and it is usually caused by high-energy trauma, such as traffic accidents and gunshots ( Meng et al, 2019 ). BPRA-caused pain is largely featured by the quick onset of pain (an effect presenting right away following the injury) and the long-lasting progress of neuropathic pain, which is described as crushing, squeezing, or burning ( Chen et al, 2019 ; Wang T. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, MALAT1 is expressed in neurons at high levels [ 38 , 145 , 186 ]. It has been shown that downregulation of MALAT1 in primary cortical neurons results in their increased excitability [ 192 ]. Results obtained by Lipovich et al showed that MALAT1 is upregulated in high-activity areas of the neocortex in patients with epilepsy, and its expression pattern suggested that it is engaged in the regulation of activity-dependent genes [ 149 ].…”
Section: Lncrnas Involved In Nuclear Body Formationmentioning
confidence: 99%
“…Hou and Xu [ 43 ] reported that the activation of astrocytes and microglia in the spinal cord played a key role in a rat model of global BPA. Meng et al [ 44 ] found that reduced lncRNA Malat1 expression might induce neuropathic pain by increasing neuronal excitability in the spinal cord via regulation of calcium flux, and Huo et al [ 45 ] reported the beneficial effects of electroacupuncture for relieving neuropathic pain in global BPA rats and also explored its function in brain plasticity. It appears that more and more researches on higher central nervous systems based on this kind of BPA models are emerging to further elucidate the networks of sensory information processing [ 15 , 46 ].…”
Section: Three Approaches Of the Animal Avulsion Modeling Procedurmentioning
confidence: 99%
“…Therapeutic strategies for the treatment of neuropathic pain are always limited by its elusive mechanisms and the incomplete understanding of nervous system plasticity after the initial injury [ 79 ], so we still need to search for different targets to treat this pain. Researches targeting the gene level have emerged with the development of genomics, and the results of the preliminary investigations seemed promising based on BPA models [ 32 , 33 , 44 ], which may be another novel route of the BPA treatment.…”
Section: Bpa-induced Neuropathic Pain and Treatmentmentioning
confidence: 99%